THE PRESENCE OF INDIGENOUS YEASTS WITH PROTEOLYTIC ACTIVITY ISOLATED FROM HOMEMADE-MOZZARELLA WHEY - Faysa UTBA; Roostita L. BALIA; Gemilang Lara UTAMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Whey, by product from cheese production, having high content of protein, can be a source of indigineous yeast with proteolytic activity. This research aims to identify indigenous yeasts with proteolytic activity from homemade-mozzarella cheese whey. There were 2 kinds of whey collected throughout the making of mozzarella, the first whey was collected after the coagulation process and the second whey was collected after mozzarella curdling process. Each types of whey were inoculated into Potato Dextrose Agar (PDA) media modified with 3% yeast extract and 10 ppm Amoxicillin and were further incubated for 48 hours in room temperature. Each colony formed were then differentiated macroscopically and purified in a separate modified PDA media for 4 times. Purified colonies were further identified under microscope and only the colonies having yeasts morphology were tested for its proteolytic activity with paving block method using Nutrient Agar plus 3% Skim Milk, with formation of clear zone were measured as proteolytic activity. Yeasts with proteolytic activity were identified using RapID yeast plus system. The results showed 7 yeasts colonies found and proteolytic activity was only found in 1 isolate with ±9.5 mm diameter of clear zone. The isolate was further brought to identification and revealed as Trichosporon beigelii.